Six sigma applications in MRO industry - Goh, Qing Rui. (2009)
Six Sigma and lean manufacturing are leveraged from manufacturing to many other industries. This is because they provide frameworks and tools that aim to reduce variations and eliminate waste. The project start off by taking a look in the MRO industry and the future forecast for the demand of the industry. Six Sigma and lean manufacturing are further discuss in details in the literature reviews on how they define waste and some possible methods to eliminate waste. The advantages and disadvantages of six sigma and the benefits of successful implementation of lean are discussed to encourage companies to adopt the framework and tools used. The framework and the tools to be used in it are discussed in details in chapter 3. In the case study, it shows how each phase of the framework is carried out, from setting the parameters to be measured to analysis of the readings and actions to tackle the problems. There are also many tools and techniques used in the framework, though some of the lean manufacturing techniques are already practiced in the case study. At the end of the six sigma project, it shows the reductions of the repair time by improving individual’s quality standards. Six Sigma frameworks is a framework that helps the user to solve problems by providing systematically step by step approaches and the tools to be used. It can be applied in all projects and help the organization to achieve continuous improvements.